Reference Management Training to Improve the Quality of Teachers' Academic Papers - Titin Sumarni; Mufaro’ah (TAAWUN, 2025)
Community service aims to find out how the reference management of SMKN 1 Bengkalis teachers is, and how to provide training on reference management using the Mendeley application to SMKN 1 Bengkalis teachers. The method of this activity is to identify objectives, prepare materials, and determine the schedule and duration of implementation. Implementation of practicums and evaluation of activities is by providing a pre-test questionnaire on understanding the material, and providing a post-test questionnaire on the material, trainers, learning processes, facilities, and implementation, and evaluation of understanding the material after participating in the training. After the pre-test was conducted, the results of the participants' understanding of reference management with Mendeley were 91.18% who had not mastered reference management with Mendeley, and those who had understood were 8.82% of the 34 training participants. To provide an understanding of reference management using the Mendeley application, the community service team provided direct training to participants, which was carried out in the SMKN 1 Bengkalis computer laboratory. After conducting reference management training with the Mendeley application for teachers at SMKN 1 Bengkalis, the results were obtained, namely that on average they were able to install the Mendeley application, were able to enter references into Mendeley both online and manually, were able to make citations into articles or manuscripts or other Academic paper, and were able to create bibliographies automatically.